1999
DOI: 10.1095/biolreprod60.5.1093
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning, Genetic Mapping, and Developmental Expression of Bovine POU5F11

Abstract: We describe isolation and characterization of the bovine ortholog of POU5F1 (bPOU5F1) encoding octamer-binding transcription factor-4 (Oct-4). The organization of bPOU5F1 is similar to its human and murine orthologs, and it shares 90.6% and 81.7% overall identity at the protein level, respectively. Transient transfection of luciferase reporter constructs in murine P19 embryonal carcinoma cells demonstrated that bPOU5F1 has a functional promoter and contains two enhancer elements, of which one is repressed by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(126 citation statements)
references
References 42 publications
8
118
0
Order By: Relevance
“…However, lower expression levels in the in vivo blastocysts may be a consequence of higher HDAC1 activity and differentiation [69]. In murine and human expanded blastocysts, expression of OCT4 was limited to the ICM [20,22,70,71] whereas in bovine and porcine blastocysts, OCT4 was expressed in both the trophectoderm and ICM [72,73]. Localization of OCT4 was diffused in the early stages of rabbit preimplantation embryos; while nuclear localization was evident in the blastocyst.…”
Section: Discussionmentioning
confidence: 99%
“…However, lower expression levels in the in vivo blastocysts may be a consequence of higher HDAC1 activity and differentiation [69]. In murine and human expanded blastocysts, expression of OCT4 was limited to the ICM [20,22,70,71] whereas in bovine and porcine blastocysts, OCT4 was expressed in both the trophectoderm and ICM [72,73]. Localization of OCT4 was diffused in the early stages of rabbit preimplantation embryos; while nuclear localization was evident in the blastocyst.…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe H3K27 methylation differences between ICM and TE cells of bovine fertilized embryos. It is worth noticing that POU5F1 protein is detected in both ICM and TE cells of bovine blastocyst (van Eijk et al 1999, Kirchhof et al 2000, and therefore is possible that the differences in H3K27me3 between pluripotent and trophoblast cells are established at later stages of bovine development.…”
Section: H3k27me3 and Pcg Gene Expression In Bovine Embryosmentioning
confidence: 99%
“…Protein expression patterns are similar to the expression patterns of POU5F1 mRNA during preimplantation development. By contrast, in cattle and swine embryos, the pattern of POU5F1 expression in the blastocyst is reported to differ, it is found in both the TE and ICM (van Eijk et al 1999, Kirchhof et al 2000. POU5F1 mRNA expression in bovine blastocysts is unclear; it has been reported to be only in the ICM (Kurosaka et al 2004), or in both the ICM and TE (Degrelle et al 2005).…”
Section: Introductionmentioning
confidence: 95%
“…In contrast, it is thought that POU5F1 protein is not suppressed in the TE of bovine embryos in vivo or in vitro. This understanding is based largely on the findings of van Eijk et al (1999) and Kirchhof et al (2000). There are some areas of confusion in these reports; however, van Eijk et al (1999) found POU5F1 protein immunostaining in ICM and TE of IVP and oviductal embryos, but no POU5F1 protein immunostaining at all in uterine embryos examined at days 14 and 16.…”
Section: Pou5f1 In Equine Embryosmentioning
confidence: 99%